Trust and Commitment Toward Mobile Payment Platform - Oktyfany Sembiring; Daniel Tumpal Hamonangan Aruan (Journal of Business and Behavioural Entrepreneurship, 2020)
With the rapid growth of online technology in financial services, Mobile Payment has becomepopular in recent years. Many studies have investigated financial innovations based oninformation and communication technology (ICT) in bank institutions. Specifically, this studyis important to explore the use of Mobile Payment provided by non-bank institutions. Thisstudy focuses on trust and commitment to improving their continuous usage intention ofMobile Payment. We argue that the advantages of Mobile Payment (Mobility, Customization,Security, and Reputation) contribute to trust and commitment. The findings of this studyillustrate that the Mobile Payment reputation has a positive effect on trust. Trust is mediatedby commitment has a positive influence on continuance intention. This study recommends thatthe topic of research needs to be explored more in order to understand and develop marketingstrategies for Mobile Payment users.